2020
DOI: 10.1093/schbul/sbaa079
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Outcomes and Network Connectivity in Early-Stage Psychosis: A Longitudinal Study

Abstract: Imaging studies in psychotic disorders typically examine cross-sectional relationships between magnetic resonance imaging (MRI) signals and diagnosis or symptoms. We sought to examine changes in network connectivity identified using resting-state functional MRI (fMRI) corresponding to divergent functional recovery trajectories and relapse in early-stage psychosis (ESP). Prior studies have linked schizophrenia to hyperconnectivity in the default mode network (DMN). Given the correlations between the DMN and beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Additionally, we observed increased fALFF in the precuneus/posterior cingulate over the course of treatment in responders; this change was not observed in non-responders. This finding complements two recent studies reporting that increased connectivity of the posterior cingulate was associated with clinical response to antipsychotic treatment in the first episode of illness 53,54 . This brain region is considered the hub of the default mode network, and is critical to the ability to shift between self-oriented processing and (external) task-oriented function mediated by dorsal prefrontal cortex 73,74 .…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, we observed increased fALFF in the precuneus/posterior cingulate over the course of treatment in responders; this change was not observed in non-responders. This finding complements two recent studies reporting that increased connectivity of the posterior cingulate was associated with clinical response to antipsychotic treatment in the first episode of illness 53,54 . This brain region is considered the hub of the default mode network, and is critical to the ability to shift between self-oriented processing and (external) task-oriented function mediated by dorsal prefrontal cortex 73,74 .…”
Section: Discussionsupporting
confidence: 89%
“…Previous longitudinal studies on FEP patients have demonstrated a link between good functional recovery and higher IQ, higher socioeconomic status, and lower severity of psychotic symptoms. 49 In addition, different outcome trajectories were linked to dynamic changes in brain functional connectivity in the default mode network, 35 (iii) follow-up patient cohorts had reduced symptomatology in PANSS and YMRS, and less medication usage compared to baseline-only patients, suggestive of higher functioning patients.…”
Section: Discussionmentioning
confidence: 99%
“…Medication information, including antipsychotics and lithium dosage, was collected at each assessment timepoint. Antipsychotics (96% second‐generation) were converted into chlorpromazine equivalents (CPZE) based on the recommendations of Gardner et al 33 We used a modified Multnomah Community Ability Scale (MCAS) to assess community functioning 34,35 …”
Section: Methodsmentioning
confidence: 99%
“…Two runs of resting state fMRI sensitive to blood oxygenation level-dependent (BOLD) contrast were collected: 6.2 min (124 time-points), TE/TR/Θ = 30 ms/3000 ms/85°, 3 mm isotropic voxels. A T1-weighted image (1.2 mm iso) was also collected for co-registration 4 …”
Section: Methodsmentioning
confidence: 99%